Plant arrangement in the expression of yield components of canola - Krüger, Cleusa Adriane Menegassi Bianchi; da Silva, José Antonio Gonzalez; Medeiros, Sandro Luis Petter; Dalmago, Genei Antonio; Sartori, César Oneide; Schiavo, Jordana (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the effects of plant arrangement on direct yield components and final production in canola, using hybrids of different development cycles. Three experiments were carried out with row spacing of 0.20, 0.40, and 0,60 m, in a randomized block design, with four replicates for each cultivation year (2008 and 2009), genotype (Hyola 432 and Hyola 61), and plant density (20, 40, 60, and 80 plants per square meter). Hyola 432 showed higher grain yield than Hyola 61, independently of year and plant density. The effects of years of cultivation influenced grain production and yield components more than the genetic potential of the cultivar and planting density. The adjustment of plant density in canola is altered by genotype and years of cultivation.